Treatment with anti-FcεRIα antibody exacerbates EAE and T-cell immunity against myelin. Issue 3 (May 2017) - Musio, Silvia; Costanza, Massimo; Poliani, Pietro Luigi; Fontana, Elena; Cominelli, Manuela; Abolafio, Gabriella; Steinman, Lawrence; Pedotti, Rosetta
Abstract : Objective: To investigate the effects of targeting the high-affinity receptor for immunoglobulin E (FcεRI), that plays a central role in allergic responses and is constitutively expressed on mast cells and basophils, in clinical disease and autoimmune T-cell response in experimental MS. Methods: Experimental autoimmune encephalomyelitis (EAE) was induced in C57BL/6 mice by immunization with myelin oligodendrocyte glycoprotein 35–55. Anti-FcεRI α-chain antibody was administered intraperitoneally. CNS immunohistochemistry, flow cytometry analysis of immune cell populations, IgE and histamine serum concentration, immune cell proliferation, and cytokine measurement were performed. In BALB/c mice, EAE was induced by immunization with myelin proteolipid protein 185–206. Results: Treatment with anti-FcεRIα antibody resulted in exacerbation of EAE and increased CNS inflammation in C57BL/6 mice. Treated mice displayed long-lasting complete depletion of basophils in the blood stream and peripheral lymphoid organs and increased antigen-induced immune cell proliferation and production of interferon-γ, interleukin (IL)-17, IL-6, and granulocyte-macrophage colony-stimulating factor. In BALB/c mice, which are T-helper (Th) 2 prone and resistant to EAE, treatment with anti-FcεRIα antibody restored susceptibility to EAE. Conclusion: Our observations that anti-FcεRIα antibody increases Th1 and Th17 responses against myelin antigen and exacerbates EAE suggest that FcεRI, basophils, and possibly other FcεRI-bearing cells that might be affected by this antibody play important roles in influencing the severity of CNS autoimmunity.